Four frameshift mutations in neurofibromatosis type 1 caused by small insertions. Issue 7 (July 1997) - Colman, S D; Abernathy, C R; Ho, V T; Wallace, M R
Abstract : We have been using heteroduplex analysis to assay individual exons within the NF1 gene in an effort to identify disease causing constitutional mutations in neurofibromatosis type 1 patients. Here we report the identification and characterisation of four insertional NF1 frameshift mutations in an analysis of exons 28-39 in a set of 78 patients. These include three 1 base pair insertions and one 2 base pair insertion. Three of these mutations can be attributed to replication slippage errors, while the mechanism behind the fourth may be related to formation of secondary structure during replication. It may be of significance that a majority of the previously reported small insertions in NF1 also lie within exons 28-39.